Nuclear Receptor CAR Requires Early Growth Response 1 to Activate the Human Cytochrome P450 2B6 Gene - Inoue, Kaoru (American Society for Biochemistry and Molecular Biology, 2008)
The nuclear receptor CAR (constitutive active/androstane receptor) is a drug-sensing transcription factor, regulating the hepatic genes that encode various drug-metabolizing enzymes. We have now characterized the novel regulatory mechanism by which the signal molecule EGR1 (early growth response 1) determines CAR-mediated activation of the human CYP2B6 (cytochrome P450 2B6) gene. The CYP2B6 enzyme metabolizes commonly used therapeutics and also activates pro-drugs. The CAR directly binds to the distal enhancer element of the CYP2B6 promoter, which is essential in converging to its drug-sensing function onto promoter activity. However, this binding alone is not sufficient to activate the CYP2B6 promoter; the promoter requires EGR1 to enable CAR to activate the CYP2B6 promoter. Upon stimulation by protein kinase C, EGR1 directly binds to the proximal promoter and coordinates the nearby HNF4α (hepatocyte-enriched nuclear factor 4α) with CAR at the distal enhancer element to activate the promoter. Thus, synergy of drug activation and the stimulation of cellular signal are necessary for CAR to activate the CYP2B6 gene.